Pathways to psychiatric care for children and adolescents at a tertiary facility in northern Nigeria - Jibril O. Abdulmalik; Shehu Sale (AOSIS, 2012)
There is limited availability of mental health services in Nigeria, and indeed most of Africa. Available services are also often under-utilized because of widespread ignorance and supernatural beliefs about the etiology of mental illnesses. The consequence, therefore, is a long and tedious pathway to care for the mentally ill, especially children and adolescents. This was a study of all new patients, aged 18 years and below, presenting over a 6 month period in 2009 (January - June) at the outpatient clinic of a tertiary psychiatric facility in northern Nigeria. A socio-demographic questionnaire was utilized, along with a record of the clinician's assessment of diagnosis for 242 patients. Subjects who had been withdrawn from school, or any previously engaged-in activity for longer than 4 weeks on account of the illness, were recorded as having disability from the illness. The children were aged 1-18 years (mean=12.3; SD=5.2) with males accounting for 51.7% (125) while 14.5% of the females (n=117) were married. Two thirds (64.5%) of the patients had been ill for longer than 6 months prior to presentation. One hundred and forty four subjects (59.5%) had received no care at all, while 36.4% had received treatment from traditional/religious healers prior to presentation. The most disabling conditions were ADHD (80%), mental retardation (77.8%), epilepsy (64.1%) and psychotic disorders (50%). There is urgent need for extending mental health services into the community in order to improve access to care and increase awareness about effective and affordable treatments.